Social Presence And Academic Interaction In Online English Learning: Perspectives Of Teachers And Students In Two Public University Contexts - Sahril Nur; Nofvia De Vega (Pascasarjana Universitas Negeri Makassar, 2023)
This study investigates the influence of social presence on online learning in Indonesian bachelor's degree programs. The objective is to identify effective strategies for enhancing students' online learning experiences by promoting social presence. Data was collected through 20 semi-structured interviews and 269 online surveys, analyzing qualitative and quantitative information. The findings highlight a significant positive relationship between social presence, engagement, happiness, and academic success in online courses. Notably, increasing one unit of social presence leads to a remarkable 10.28-point improvement in academic achievement. These results emphasize the importance of prioritizing interaction, collaboration, and community building in the online learning environment. Policymakers and educators can utilize these insights to design effective online courses tailored to bachelor's degree students' unique needs. By incorporating strategies that foster social presence and create a sense of belonging, educators can enhance students' engagement, satisfaction, and overall learning experiences. Therefore, this research underscores the significance of social presence in online learning and provides valuable insights to improve students' academic achievements and online learning experiences.